Evolução da estrutura agrária do Estado do Ceará - Silva, Luiz Artur Clemente da (1982)
This paper deals with the study of the evolution of the agrarian structure in the State of CeaH, Brazil, from 1920 on. The agrarian census issued by IBGE (Brazilian Institute of Geography and Statistics) were used as data source and the following occurrences were observed: 1) Land tenure was highly concentrated in the State of Cear, in 1920. Furthermore inequality increased in the following decades. 2) The rate of effective land occupation rose from 59% in 1940 to $2% in 1970. This movement was followed by an increase of the cultivated land, mainly in those properties up to 10 ha of total area. These properties dedicated 71% of their lands to crops in 1970, while those with areas of 1,000 ha or more dedicated only 9%. 3) From 1960 to 1975 the increase of the degree of concentration of land tenure was not so pronunced because of the multiplication of the number of small holdings in the State from 1970 to 1975. This process was common to all regions of the State but it was more evident in the Northwest. However the highest concentration occurred in the region of Fortaleza and the lowest concentration occurred in the South, which is an old region of colonization where the properties were already subdivided by inheritance. 4) The labor force in agriculture in the State, from 1960 to 1975, increased at a geometrical rate of 1.5%; the highest population concentration occurred in properties up to 10 ha of area and the growth rate was 6% in the same period which made these properties use labor more intensively. 5) The type of labor used in the sector is predominatly familiar, mainly in the smaller properties, while in the larger ones there is a predominancy of the categories employee ("assalariado") and sharecropper ("parceiro"); this latter type occurs because this is a way by which the big farmers obtain an extra profit from lands that otherwise would not be used. 6) The level of mechanization and use of ferti lizers is too low in the State and among those farmers using fertilizers in 1975, 71.8% used only organic manure.